"Magic" Ionization Mass Spectrometry - Trimpin, Sarah (J Am Soc Mass Spectrom, 2015)
The systematic study of the temperature and pressure dependence of matrix-assisted ionization (MAI) led us to the discovery of the seemingly impossible, initially explained by some reviewers as either sleight of hand or the misinterpretation by an overzealous young scientist of results reported many years before and having little utility. The “magic” that we were attempting to report was that with matrix assistance, molecules, at least as large as bovine serum albumin (66 kDa), are lifted into the gas phase as multiply charged ions simply by exposure of the matrix:analyte sample to the vacuum of a mass spectrometer. Applied heat, a laser, or voltages are not necessary to achieve charge states and ion abundances only previously observed with electrospray ionization (ESI). The fundamentals of how solid phase volatile or nonvolatile compounds are converted to gas-phase ions without added energy currently involves speculation providing a great opportunity to rethink mechanistic understanding of ionization processes used in mass spectrometry. Improved understanding of the mechanism(s) of these processes and their connection to ESI and matrix-assisted laser desorption/ionization may provide opportunities to further develop new ionization strategies for traditional and yet unforeseen applications of mass spectrometry. This Critical Insights article covers developments leading to the discovery of a seemingly magic ionization process that is simple to use, fast, sensitive, robust, and can be directly applied to surface characterization using portable or high performance mass spectrometers. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13361-015-1253-4) contains supplementary material, which is available to authorized users.